Web technological path and digital order in Latin America: Historical reflections from Brazil - Berrío-Zapata, Cristian [UNESP]; Jorente, María José Vicentini [UNESP]; Santana, Ricardo Cesar Gonçalves [UNESP] (My University, 2014)
The emergence of the digital order renewed the Victorian civilizing ideal and strengthened a world order of techno-economic dependence. The new grand narrative is the urgency of digital transformation of societies; a dream pursued without reflection by the populations of the periphery that ended into in a collision between McLuhan's two informational orders: cold and hot societies. Latin America as part of the periphery did not participate in the development of the informatic technologies and its historical legacy made the appropriation of these technologies more difficult. This paper examines the historical circumstances of this process: the development of a discourse around the digital networks, the consequences of this social construction in the region, the fragile efforts of Brazil to create technology, and the entrance of IT networks in the region. The results showed that the status of this kind of research in the region is weak so we alert about its consequences. We concluded that to create an informational order that may serve as a space of self-affirmation, freedom and heterogeneity, it is necessary to have a deep knowledge of the social and historical context that created its basic technologies, but Latin America is indifferent in such regard. Information Science has a central role in the region within this process but it has not developed it yet.
Trayectoria tecnológica Web y el orden digital en Latinoamérica: Reflexiones históricas desde Brasil
Keywords: History; ICT; Internet; Latin America; Web